2014
DOI: 10.1139/cjfr-2014-0110
|View full text |Cite
|
Sign up to set email alerts
|

Smoke management of wildland and prescribed fire: understanding public preferences and trade-offs

Abstract: Smoke from forest fires is a serious and increasing land management concern. However, a paucity of information exists that is specific to public perceptions of smoke. This study used conjoint analysis, a multivariate technique, to evaluate how four situational factors (i.e., smoke origin, smoke duration, health impact, and advanced warning) influence public tolerance of smoke in the northern Rocky Mountains and south-central United States. Separate analyses were performed for subgroups, based on community type… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 23 publications
0
15
0
1
Order By: Relevance
“…The importance of these factors for tolerance of smoke emissions has been demonstrated across additional studies, with some important differences. Recent studies have also found that smoke tolerance is impacted by the smoke source, however the most acceptable source varied from fires started by lightning strikes (Blades et al 2014) to wildfires under active suppression (Engebretson et al 2016) to uncontrolled wildfires (Olsen et al 2017). Present in each of these studies, however, was a moderate to high level of tolerance (or acceptance) of smoke emissions, including those from prescribed-natural fires and prescribed burns.…”
Section: Perceptions Of Prescribed Fires and Smoke Emissionsmentioning
confidence: 99%
See 2 more Smart Citations
“…The importance of these factors for tolerance of smoke emissions has been demonstrated across additional studies, with some important differences. Recent studies have also found that smoke tolerance is impacted by the smoke source, however the most acceptable source varied from fires started by lightning strikes (Blades et al 2014) to wildfires under active suppression (Engebretson et al 2016) to uncontrolled wildfires (Olsen et al 2017). Present in each of these studies, however, was a moderate to high level of tolerance (or acceptance) of smoke emissions, including those from prescribed-natural fires and prescribed burns.…”
Section: Perceptions Of Prescribed Fires and Smoke Emissionsmentioning
confidence: 99%
“…In addition to the origin of the smoke, a number of other tolerance influencers emerged. Blades et al (2014) found that tolerance was impacted by public warning in advance, expected severity of health effects from the smoke (particularly at unhealthy levels for everyone or sensitive populations), and smoke duration. Higher levels of tolerance emerged if resource managers openly stated the forest health objectives behind the prescribed fire event (Engebretson et al 2016).…”
Section: Perceptions Of Prescribed Fires and Smoke Emissionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Balancing the management of wildland fires in a way that preserves ecosystem function and maintains air quality to protect human health remains a substantial research and environmental policy challenge (Haikerwal et al 2015;Schweizer and Cisneros 2016). Adding to this challenge is a heterogeneous mix of communities with different views of prescribed fire and tolerance to wildland fire smoke (Blades et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The 2014 study completed by Blades determined that the most important factors with regard to the publics' forbearance of smoke depends on the origin of the smoke and advanced public warnings (Blades, Shook, and Hall 2014).…”
Section: Surveys Public Perceptionsmentioning
confidence: 99%